Methods of Use of Terminal Forecast Information for Protection of the Population From Emergency Emergencies - A., Rayimkulov; U, Norkulov M.; A, Turdikulov A. (European Journal of Life Safety and Stability (2660-9630), 2022)
The article discusses ways to reduce the secondary effects of strong earthquakes in Uzbekistan, as well as measures to effectively protect the population from emergency situations associated with earthquakes.